Revisiting Autoimmunity in Chronic Lymphocytic Leukemia: Prognostic Value of Positive Direct Antiglobulin Test in a Retrospective Study and Literature Review - Ahmed SA; Abdallah GEM; Aly MM; Abdelsalam EMN; Mohammed Saleh MF (Journal of Blood Medicine, 2021)
Shimaa A Ahmed,1 Ghada EM Abdallah,2 Mai M Aly,2 Eman M Nagiub Abdelsalam,3 Mostafa F Mohammed Saleh2 1Department of Internal Medicine, Faculty of Medicine, South Valley University, Qena, Egypt; 2Clinical Hematology Unit, Department of Internal Medicine, Faculty of Medicine, Assiut University, Assiut, Egypt; 3Department of Clinical Pathology, Faculty of Medicine, Assiut University, Assiut, EgyptCorrespondence: Mostafa F Mohammed Saleh Tel +201013701057Fax +2088-2332278-2080278Email mostafafaisal2017@yahoo.comIntroduction: A positive direct antiglobulin test (DAT) with or without autoimmune hemolytic anemia is a frequent finding in chronic lymphocytic leukemia (CLL). The heterogenic clinical course of CLL mainly depends on different pathogenetic mechanisms which appears in a form of variable biological and clinical features. These features allow stratification of patients into subsets with different outcomes.Patients and Methods: We evaluated the DAT as a prognostic marker in 120 CLL patients treated with chemoimmunotherapy. Clinical and laboratory features, treatment response, and survival outcomes of CLL patients were assessed in relation to their DAT test status. Additionally, the English literature was extensively reviewed regarding the prognostic impact of a positive DAT in CLL.Results: DAT positivity was detected in 36 patients (30%) and was associated advanced disease staging (P = 0.03). No correlations were found with other clinical, laboratory, or biological factors such as ZAP-70 or CD38. Both a positive DAT and an Eastern Cooperative Oncology Group performance status > 2 were predictors for non-response to first-line treatment in the multivariate analysis (OR = 0.3, 95% CI: 0.12– 0.8 and OR = 0.2, 95% CI: 0.08– 0.8, respectively). The five-year progression-free survival was significantly lower in the DAT-positive group (P = 0.004). No significant association was found with overall survival (P = 0.2). Sixteen reports analyzing more than 11,000 patients were identified in our review.Conclusion: In conclusion, DAT positivity in CLL patients is associated with poor response to treatment and disease progression.Keywords: autoimmunity, chronic lymphocytic leukemia, direct antiglobulin test, autoimmune hemolytic anemia